Distribution, aerodynamic characteristics, and removal of the major cat allergen Fel d 1 in British homes. Issue 1 (January 1998) - Custovic, A; Simpson, A; Pahdi, H; Green, R M; Chapman, M D; Woodcock, A
Abstract : BACKGROUND: Sensitisation to cat allergen (Fel d 1) is an important risk factor for asthma in the UK. A study was undertaken to investigate the distribution of cat allergen in British homes, the aerodynamic characteristics and particle size distribution of airborne Fel d 1, and the method of removing it. METHODS: Dust was collected from 50 homes with a cat and from 50 homes without a cat, and airborne levels of Fel d 1 were measured in 50 homes with a cat and 75 homes without a cat. Particle size distribution was determined using an Andersen sampler (8 hours/day) in 10 homes with cats. This was repeated on five separate days in a house with four cats, and then one, two, four, seven, and 14 days after the cats were removed from the living room area. The effect of high efficiency particulate air (HEPA) cleaner on airborne levels of Fel d 1 was investigated in seven homes with cats. Samples were collected on two separate days from two rooms of each house concurrently, one of which contained the cat, one day with the HEPA cleaner on and the other day as a control. Three one hourly samples were collected over a nine hour period (baseline, 4-5 hours, 8-9 hours) using a high volume dust sampler (air flow rate 60 l/min) and the air sample was collected onto a microglass fibre filter (pore size 0.3 micron). RESULTS: Fel d 1 concentrations were much lower in houses without a cat than in those with a cat (260-fold difference (95% CI 167 to 590) in living room carpets: geometric mean (GM) 0.9 microgram/g (range 0.06-33.93) versus 237 micrograms/g (range 2.8-3000); 314-fold difference (95% CI 167 to 590) in upholstered furniture: 1.21 micrograms/g (range 0.06-61.9) versus 380 micrograms/g (range 7.1-6000); 228-fold difference (95% CI 109 to 478) in bedroom carpets: 0.24 microgram/g (range 0.06-2.24) versus 55 micrograms/g (range 0.06-2304); and 215-fold difference (95% CI 101 to 456) in mattresses: 0.2 microgram/g (range 0.06-2.3) versus 55 micrograms/g (range 0.06-3400). Airborne levels of Fel d 1 were detected in all houses with cats, and the levels varied greatly between the homes (range 0.7-38 ng/m3). Low concentrations of airborne Fel d 1 (range 0.24-1.78 ng/m3) were found in 22 of 75 homes without a cat. Although airborne Fel d 1 was mostly associated with large particles (> 9 microns, approximately 49% of the allergen recovered), small particles (< 4.7 microns) comprised approximately 23% of the total airborne allergen. Total airborne Fel d 1 was reduced by 61.7% two days after removal of the cat but this was due predominantly to the decrease in larger particles (> 4.8 microns) which fell to 13% of their baseline level. Fel d 1 levels associated with small particles (< 4.8 microns) remained largely unchanged on days 1, 2 and 4 and then slowly decreased to 33% of the baseline levels at day 14. With HEPA cleaner a significant reduction in airborne Fel d 1 was observed compared with the control sampling (GM 5.04-0.88 ng/m3 versus 3.79-1.56 ng/m3 at baseline and 8 hours, active versus control group; p = 0.008). CONCLUSIONS: Airborne Fel d 1 was detectable in undisturbed conditions in all homes with cats and in almost a third of homes without cats. In houses with cats a significant proportion (23%) of airborne Fel d 1 was associated with small particles (< 4.7 microns diameter). Removal of the cat from the living room and bedroom areas of the home and the use of HEPA air cleaner reduced airborne levels of cat allergen in homes with cats, but the reduction following cat removal was not evenly spread across the particle size range.